Biology and control of insect pests - International Center for Tropical Agriculture (International Center for Tropical Agriculture, 1985)
Two bean cv. were exposed to known levels of attack of nymphs and adults of Empoasca kraemeri for 14-day periods at different growth stages. On av., Diacol-Calima and EMP 81 suffered a yield loss of 16.5 and 14.6 kg/ha, resp., per insect/leaf/14-day period. A study of the insect complex attacking fruiting structures of beans was carried out at CIAT-Palmira. It was found that Cydia fabivora and Epinotia aporema attack physiologically mature pods. The biology of the slug Vaginulus plebeius and of Zabrotes subfasciatus on beans was also studied. (CIAT)